1987
DOI: 10.2307/3430454
|View full text |Cite
|
Sign up to set email alerts
|

Second Chronological Supplement to the Carcinogenic Potency Database: Standardized Results of Animal Bioassays Published through December 1984 and by the National Toxicology Program through May 1986

Abstract: This paper is the second chronological supplement to the Carcinogenic Potency Database, published earlier in this journal (1,2,4). We report here results of carcinogenesis bioassays published in the general literature between January 1983 and December 1984, and in Technical Reports of the National Cancer Institute/National Toxicology Program between January 1983 and May 1986. This supplement includes results of 525 long-term, chronic experiments of 199 test compounds, and reports the same information about eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…We have performed analyses ofa number ofdifferent rodent carcinogenicity databases including the NTP rodent bioassay (9,10) and the compilation of Gold and associates (21)(22)(23) which includes TD50 values. Analyzing these databases allowed us to identify the structural features responsible for the probability of carcinogenicity (i.e., the qualitative aspect of the analysis).…”
Section: Comparison Of Some Carcinogenicity Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have performed analyses ofa number ofdifferent rodent carcinogenicity databases including the NTP rodent bioassay (9,10) and the compilation of Gold and associates (21)(22)(23) which includes TD50 values. Analyzing these databases allowed us to identify the structural features responsible for the probability of carcinogenicity (i.e., the qualitative aspect of the analysis).…”
Section: Comparison Of Some Carcinogenicity Databasesmentioning
confidence: 99%
“…Applying the QSAR CASE analysis to the database assembled by Gold et al (21)(22)(23), which includes TD50 values, indicated that the data could be used to generate QSAR relationships for individual databases (i.e., mouse and rat separately) which, in turn, can be used to project carcinogenic potencies based upon the QSAR contribution of individual biophores (Table 11). [The TD50 value is defined as the lifetime dose (milligrams per kilogram per day) that reduces by one-half the lifetime chance of remaining tumor-free (24).…”
Section: Comparison Of Some Carcinogenicity Databasesmentioning
confidence: 99%
“…This descriptor (biophore) was originally recognized during structureactivity relationship (SAR) studies of diethylstilbestrol (2) and tamoxifen and toremifene (3), using the SAR expert systems computer automated structure evaluator (CASE) and multiple case (MULTICASE). This biophore was derived from the CASE/MULTICASE learning set of murine carcinogens (4)(5)(6)(7)(8). Based on its presence in carcinogenic estrogens, we suggested that the 2D biophore represented a ligand binding site on an estrogen receptor (1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to molecular fragments, MULTICASE considers two-dimensional distance descriptors. Compounds (6) and the CPDB data assembled by Gold and associates (7)(8)(9)(10)(11) …”
Section: Introductionmentioning
confidence: 99%